A Review of The Sundanese Scale Theory - Sasaki, Mariko; Masunah, Juju (Harmonia: Journal of Arts Research and Education, 2021)
This article aims to discuss Kusumadinata’s scale theory in Sundanese music which has been taught in educational institutions in West Java, Indonesia. According to Kusumadinata’s scale theory, sorog and pelog are scales derived from salendro scale in gamelan salendro performance. In my previous research, I investigated three genres of Sundanese performing arts which have existed since the Hindu era, namely goong renteng, pantun, and tarawangsa. The results indicate that the pelog scale has independently existed since the Hindu era. Then, I analyzed the phenomenon that occurs in the gamelan salendro performance, i.e., its melody (rebab and vocals) conventionally modulate into scale ‘like sorog’, occasionally into scale ‘like pelog’, whereas the instruments of gamelan are in the salendro scale. However, the analysis on the sorog in the previous research was not enough, so that in this paper, I will focus on the sorog. To find out the relationship between melody (vocal and rebab) and gamelan instruments, I examined the actual performances of gamelan salendro and wayang golek purwa. It became clear that the salendro scale derives four types of sorog. The findings of this study indicate that sorog has existed since the 19th century by this phenomenon, and the scale now called sorog is a scale derived from salendro.